Reduction of NADPH-oxidase activity ameliorates the cardiovascular phenotype in a mouse model of Williams-Beuren Syndrome. - Victoria Campuzano (PLoS Genetics, 2012)
A hallmark feature of Williams-Beuren Syndrome (WBS) is a generalized arteriopathy due to elastin deficiency, presenting as stenoses of medium and large arteries and leading to hypertension and other cardiovascular complications. Deletion of a functional NCF1 gene copy has been shown to protect a proportion of WBS patients against hypertension, likely through reduced NADPH-oxidase (NOX)-mediated oxidative stress. DD mice, carrying a 0.67 Mb heterozygous deletion including the Eln gene, presented with a generalized arteriopathy, hypertension, and cardiac hypertrophy, associated with elevated angiotensin II (angII), oxidative stress parameters, and Ncf1 expression. Genetic (by crossing with Ncf1 mutant) and/or pharmacological (with ang II type 1 receptor blocker, losartan, or NOX inhibitor apocynin) reduction of NOX activity controlled hormonal and biochemical parameters in DD mice, resulting in normalized blood pressure and improved cardiovascular histology. We provide strong evidence for implication of the redox system in the pathophysiology of the cardiovascular disease in a mouse model of WBS. The phenotype of these mice can be ameliorated by either genetic or pharmacological intervention reducing NOX activity, likely through reduced angII-mediated oxidative stress. Therefore, anti-NOX therapy merits evaluation to prevent the potentially serious cardiovascular complications of WBS, as well as in other cardiovascular disorders mediated by similar pathogenic mechanism.